(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The paper examines the positions taken by European feminists during World War I, a fact which divided waters between the pacifists and war- mongers. Pacifists women held the International Congress of The Ha- gue in 1915 that requested the immediate end of the war. The pacifist women of social democracy also met in Bern, Switzerland as opposed to their male peers, who voted for war credits. The war broke feminism that could only compose herself about demand rights after 1918. The paper also analyzes the thought of Virginia Woolf against the war in her book “Three Guineas”. She blames the patriarchy by wars, but she says that wars can be sustained with the cooperation of women.